PERSEPSI ANAK MUDA DI SURABAYA MENGENAI COFFEE SHOP SEBAGAI GAYA HIDUP MASYARAKAT PERKOTAAN - Pratiwi, Rismawardani Wahyu; S. I.Kom., M.A., Awang Dharmawan (Universitas Negeri Surabaya, 2022)
Changes in lifestyle have hit the people of big cities in Indonesia, marked by the proliferation of places to enjoy stylish coffee, the beauty industry, the fashion industry, shopping centers. Consumption of something is now not only based on the use value of the product but on the consumer's personal values and prestige. This study aims to determine and interpret the perceptions of young people in Surabaya about coffee shop as a lifestyle. Using phenomenological methods and types of qualitative research with data collection techniques through interviews. The result of this research is that young people in Surabaya come to coffee shop not only to fulfill their coffee addict needs, but also come to get validation from the surrounding environment that what they do is in accordance with the lifestyle of today's urban communities. Through the style of appearance, speak using slang style, and other things that represent that he is in the modern era. Keywords: Perception, youth, lifestyle, coffee shop